Treatment of multiple refractory ankle ulcerations in thromboangiitis obliterans: A case report. Issue 20 (May 2018) - Huang, Zheng-Hao; Kuo, San-Yuan; Chiu, Yu-Hsiang; Chen, Hsiang-Cheng; Lu, Chun-Chi
Abstract: Rationale: Thromboangiitis obliterans (TAOs, or Buerger's disease) present as a non-atherosclerotic segmental occlusive vasculitis within medium- and small-sized blood vessels. TAO frequently occurs in young adults and is associated with cigarette smoking. At present, there are no accurately defined treatments for TAO. Patient concerns: A 34-year-old Asian woman with a 20-year history of heavy cigarette smoking and recurrent, small, and self-limited lower limb ulcerations since adolescence, presented with persisting unhealed ulcerations on both ankles for 6 months. Her wound healing response was poor following the 2-month administration of colchicine, prednisolone, hydroxychloroquine, and mycophenolic acid. Diagnosis: The patient was diagnosed with TAO with hyperimmunoglobulin E and refractory ulcerations on her ankles. Interventions: The patient received monthly omalizumab (300 mg) and previous medications for 2 months and shifted to omalizumab and colchicine without mycophenolic acid and hydroxychloroquine because of onychomadesis, which was considered to be a possible adverse drug reaction. Outcomes: The wounds healed almost completely. The administration of omalizumab and colchicine will be continued until they the wounds are fully healed. Lessons: Mycophenolic acid has a limited function in TAO treatment, especially in cases of refractory skin ulcerations. Omalizumab can be a valuable treatment option for patients with TAO and hyperimmunoglobulin E.